Acceptance of Mobile Food Delivery Application: Extending UTAUT2 with Perceptions of Food Safety and Food Delivery Hygiene - Nurdinintya Athari; Augustina Asih Rumanti; Hilman Dwi Anggana (Performa: Media Ilmiah Teknik Industri, 2025)
The government implemented policies for working and schooling from home and restricted access to public spaces during the COVID-19 pandemic. This policy requires people to stay at home, minimize going home, social distancing, and follow health protocols. To meet their daily consumption needs, the community purchased raw ingredients or ready-to-eat food online using the Mobile Food Delivery Application (MFDA). During the pandemic, the public's use of MFDA technology has increased significantly. Factors that are suspected to influence the increase in MFDA usage are the aspects of food safety and hygiene, as well as the delivery process. According to MFDA providers, pandemic conditions increase competition between providers in providing the best services that provide user safety and comfort. Therefore, the purpose of this research is to investigate the factors that influence consumer behavior toward the acceptance of MFDA so that providers can formulate appropriate strategies to win the competition. The research model is based on the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model and several models in previous studies related to acceptance of MFDA. The survey was conducted on 244 MFDA users in the Bandung Raya area during the pandemic. Data processing is using Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of this study show that Facilitating Conditions, Habits, Perceptions of Food Safety, and Food Delivery Hygiene influence the Behavioral Intention to use MFDA during the pandemic. The results of this research can be used by providers to improve strategies for winning the market in pandemic conditions or other disaster conditions in the future.